2008
DOI: 10.2741/3045
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemokines during herpes simplex virus-1 infection

Abstract: Herpes simplex virus-type 1 is among the most prevalent and successful humans pathogens. Although infection is largely uncomplicated in the immunocompetent human host, HSV-1 infection can cause blinding corneal disease, and individuals with defects in innate or adaptive immunity are susceptible to herpes simplex encephalitis. Chemokines regulate leukocyte trafficking to inflamed tissues and play a crucial role in orchestrating the immune response to HSV-1 infection. In this review we will focus on the pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 119 publications
3
37
0
2
Order By: Relevance
“…3 Furthermore, this process is initiated by the expression of several chemokines. Using endpoint PCR, early studies identified several chemokines that were induced following ocular HSV-1 infection including CXCL1, CXCL2, CXCL10, CCL2, and CCL4.…”
mentioning
confidence: 99%
“…3 Furthermore, this process is initiated by the expression of several chemokines. Using endpoint PCR, early studies identified several chemokines that were induced following ocular HSV-1 infection including CXCL1, CXCL2, CXCL10, CCL2, and CCL4.…”
mentioning
confidence: 99%
“…In comparison, a viral mimic such as poly I:C was capable of upregulating gIP, CXCd, CK1, CK3, CK5B, CK7A and CK12, therefore, the differences that may arise from the profile induced by poly I:C and that produced by the two viruses may give us an indication of alterations provoked specifically by the virus most probably in its benefit. These viral-induced alterations could be either up or down-modulations of one specific chemokine, as has been demonstrated in many different mammalian viral models [9,[36][37][38][39]. Preliminary studies performed in our group using eukaryotic expression vectors, revealed some immune effects of CK5B, CK6 and CK7A, previously catalogued as ''inducible'' CC chemokines [29].…”
Section: Discussionmentioning
confidence: 87%
“…The ultimate goal is to understand HSV-1 neurotropism, namely the predilection of the virus to infect and replicate in specific brain regions and cells. The ex vivo brain system, that has extensively been used in physiological studies of the central nervous system (Corner et al, 2005;House et al, 1998), lacks aspects of complete neuronal circuits and the immune response; both are known to be important factors in HSV encephalitis (Barnett et al, 1994;Conrady et al, 2010, Norgren & Lehman, 1998Wuest & Carr, 2008). This experimental system, on the other hand, with its normal tissue architecture, facilitated the study of factors, such as extra-cellular molecules, that affect virus-tissue interactions, and thus it complements previous in vivo and tissue culture studies.…”
Section: Discussionmentioning
confidence: 99%